AN EXPERIMENTAL STUDY PERFORMED TO COMPARE THE HEPATOPROTECTIVE ACTIVITY OF ALOE VERA AND SILYMARIN IN CARBON TETRA CHLORIDE (CCL4)-INDUCED HEPATOTOXICITY IN ALBINO RABBITS - JAIN, ANURAG; JAIN, SUCHI; KOTHARI, NITIN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to compare the hepatoprotective activity of Aloe vera and Silymarin in carbon tetrachloride (CCl4)-induced hepatotoxicity in albino rabbits. Methods: The study was conducted on 18 healthy albino rabbits of either sex weighing 1.5–2.0 kg, divided into three groups. Hepatotoxicity was induced in rabbits by administering CCl4(0.05 mg/kg) intraperitoneally. Alcoholic extracts of leaves of A. vera and Silymarin were administered orally for 20 days from day 1 to day 20 in the doses of 100mg/kg/day with the help of a syringe in groups II and III respectively. Results: Group I: There was an increase in the level of serum transaminase (p<0.001), serum alkaline phosphatase (p<0.001), serum bilirubin (p<0.001), and a decrease in serum albumin (p<0.001) due to hepatotoxic effect of CCl4 when compared to day 0 of the same group. Group II: A. vera extract was found to reduce the level of aspartate transaminase (p<0.0001), alanine transaminase (p<0.0001), serum alkaline phosphatase (p<0.0001), serum bilirubin (p<0.0001), and increase in serum albumin (p<0.0001). Group III: Silymarin was found to reduce the level of aspartate transaminase (p<0.0001), alanine transaminase (p<0.0001), serum alkaline phosphatase (p<0.0001), serum bilirubin (p<0.0001), and increase in serum albumin (p<0.0001). The findings of Group II and Group III were found to be statistically highly significant when compared with Group I. On histopathology, Group II showed maximum reduction in fatty changes compared to Group III. Conclusions: A. vera extract and Silymarin both showed a decline in hepatotoxic effects induced by CCl4. Comparatively, A. vera exhibited higher protection in restoration of liver function and regeneration of liver cells than Silymarin.